Integrating Eco-Pedagogy Environmental Literacy Boards in Teaching Descriptive Writing - Siti Sofiyah; Nofitasari Nofitasari; Ami Silmia; Husni Mubarok (Lembaga Pendidikan Hikmatun Najah Blora, 2025)
Environmental education has become increasingly important in fostering students’ awareness, responsibility, and sustainable behavior. However, in many elementary schools, writing instruction particularly descriptive writing remains less engaging due to low student motivation and the limited use of contextual learning media. In response to these challenges, this study aims to describe the effectiveness of eco-pedagogy based environmental literacy boards in improving descriptive writing skills among fourth-grade students at MI Raudlatut Tholibin Sambung. Using a qualitative case study design, data were collected through observation, interviews, and documentation involving 25 students. The findings reveal a significant improvement in descriptive writing performance, with an average increase of 100% across content completeness, diction accuracy, and paragraph coherence. The environmental literacy boards provided visual and contextual stimuli that encouraged students to write more expressively and cohesively. Moreover, the media enhanced students’ ecological awareness and sense of responsibility through reflective writing activities. Integrating eco-pedagogy into language instruction proved effective in fostering literacy competence and environmental empathy, aligning with the Profil Pelajar Pancasila vision of critical, creative, and ethical learners.